PENGARUH REWARD DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT TOP PROPERTI INDONESIA - Nadia Anggraeni; Ahmad Nazir (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstract. This research aims to determine the influence of rewards and organizational culture on employee performance at PT Top Properti Indonesia, both partially and simultaneously. This type of associative research with a quantitative approach. The research sample was 73 respondents. The data analysis methods used in the research include instrument tests consisting of validity tests, reliability tests, classic assumption tests consisting of normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, correlation coefficients, coefficient of determination tests, hypothesis tests consisting of partial t tests and simultaneous f tests. The research results show that rewards have an influence on employee performance with a calculated t value > t table or (8.993 > 1,994) and a significance value of 0.000 < 0.05. Organizational culture has a positive and significant influence on employee performance with a calculated t value > t table or (9.051 > 1,994) and a significance value of 0.000 < 0.05. Rewards and Organizational Culture have a positive and significant influence on employee performance with a calculated F value > F table or (57.033 > 3.130.) and a significance value of 0.000 < 0.05. The results of the R-square value show that Reward and Organizational Culture together have an influential contribution to employee performance variables of 62%, while the remaining 38% is influenced by other factors or variables that were not studied. Keywords: Reward, Organizational Culture, Employee Performance